2015
DOI: 10.5152/jtgga.2015.0147
|View full text |Cite
|
Sign up to set email alerts
|

Method comparison between Munich II and III nomenclature for Pap smear samples

Abstract: Keywords: Munich nomenclature II, Munich nomenclature III, Pap smear Received: 30 July, 2015 Accepted: 14 October, 2015 Method

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 8 publications
0
10
0
Order By: Relevance
“…Anal smears were stained with Papanicolaou reagent and then evaluated by a PAP‐trained pathology specialist. The diagnostic classification was performed according to the Munich Nomenclature II (Table ) …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Anal smears were stained with Papanicolaou reagent and then evaluated by a PAP‐trained pathology specialist. The diagnostic classification was performed according to the Munich Nomenclature II (Table ) …”
Section: Methodsmentioning
confidence: 99%
“…The diagnostic classification was performed according to the Munich Nomenclature II (Table 1). 25 Anoscopy A board-certified specialist for proctology performed conventional diagnostic anoscopies. Clinical evaluation and mucosa biopsies from suspicious regions were performed upon staining of the suspicious areas with 3% acetic acid using a 4 mm skin biopsy punch (Stiefel Laboratorium AG, Offenbach, Germany).…”
Section: Ain Cytobrush Screening and Anal Cytology By Pap Smear Assesmentioning
confidence: 99%
“…Cytological examinations were interpreted according to Munich Nomenclature for the Cytological Diagnosis of Cervical Pap smears [ 17 ]. In our study cytological findings were classified as abnormal (PAP III+) if the pathologist reported PAP III (unclear finding corresponding in the Bethesda classification system to ASCUS), PAP IIID (cells of mild or moderate dysplasia corresponding in the Bethesda classification system to LSIL or HSIL respectively), PAP IVA (cells of severe dysplasia or carcinoma in situ corresponding in the Bethesda classification system to HSIL or AIS, respectively), PAP IVB (cells of invasive carcinoma not safely excluded, corresponding in the Bethesda classification system to HSIL or AIS with features suspicious for invasion, respectively) or PAP V (cells of invasive cervical carcinoma).…”
Section: Methodsmentioning
confidence: 99%
“…Raman imaging was used to analyze human epithelial cervical cells obtained from 96 patients classified to eight groups according to Munich III system [51] and HPV tests: I/HPV − , IIa/HPV − , IIa/HPV + , LSIL/HPV − , LSIL/HPV + , HSIL/HPV − , HSIL/HPV + and cancer cells -squamous cell carcinoma (SCC/HPV + ; for number of patients see Table S1). The cluster analysis (CA, a statistical method enabling to classify spectra according to a chemical composition) was used to determine distribution of main subcellular structures.…”
Section: Subcellular Distribution Of Glycogen In Cervical Epithelial Cellsmentioning
confidence: 99%
“…As HPV induces activation of various signal transduction pathways related to metabolic activity of cervical cells, in this work, Raman microscopy with subcellular resolution has been used to study distribution of chemical components in epithelial cervical cells collected from HPV positive or negative patients. Patients were classified according to the Munich III system [51,52] to I, IIa, IIID-1 IIID-2 (IIID-1 and IIID-2 corresponding to Bethesda LSIL-low-grade squamous intraepithelial lesion and HSIL-high-grade squamous intraepithelial lesion groups, respectively) and cancer groups, in the followed text called I, IIa, LSIL and HSIL as Bethesda nomenclature is commonly used in the literature. Investigation of Raman data, supported by the chemometric data analysis and periodic acid-Schiff (PAS) staining, demonstrates that for cervical cells with large (diameter over 10 µm) cell nuclei, the level of glycogen is significantly decreased in comparison to low-diameter nuclei cells.…”
Section: Introductionmentioning
confidence: 99%